Antecedent Factors of Financial Management Behavior: Evidence from a Study on E-Wallet User Students - Aisyah, Rizka Nur; Widagdo, Bambang; Warsono, Warsono (Business Innovation Management and Entrepreneurship Journal, 2023)
Financial technology or fintech use continues to proliferate, and more people are starting to manage their finances digitally. Today's Financial management behavior tends to be more security-oriented and uses technology to manage finances more efficiently. This study aims to determine the effect of financial knowledge, financial technology payments, and parental income on financial management behavior. Respondents in this study were students of the Faculty of Economics and Business, University of Muhammadiyah Malang, and the population was students of classes 2019, 2020, and 2021 with a sample calculation using the Slovin formula of 100 people. The analytical tool used in this study is multiple linear regression analysis with SPSS programs. The data collection method used in this study is an online questionnaire with a Google form. The results of this study simultaneously show that financial knowledge, financial technology payments, and parental income significantly positively affect student financial management behavior. This finding highlights the importance of education related to financial management and increasing financial knowledge in students.